PENGARUH MINAT DAN MOTIVASI BELAJAR TERHADAP PRESTASI SISWA PADA PELAJARAN PPKN - Indah Yuniarti; Minto Santoso; M. Iqbal Baihaqi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
The aims of this research is influence of motivation and interest to learn on student achievement at class XI Civics at SMAN 1 Kademangan for the academic year 2021/2022. This research uses descriptive quantitative research. This population amounted to 150 students, the sample of this research is 60 samples. Ssampling technique of this research is the selected sample technique. The data collection technique of this research used a questionnaire and documentation. The data analysis techniques of this research are validity, reliability, normality, multicollinearity, T test and F test. The results of this study can be seen from the results of the partial T test that there is a positive influence between interest in student achievement in class XI SMAN 1 Kademangan, namely the calculated T value. interest in learning (X1) a number of (5,768)T table (2.002) In addition, partially there is a positive influence between motivation on student achievement in class XI IPS SMAN 1 Kademangan the results of the value of T count learning motivation (X2) a number of (2,247)T table (2.002). Based on the F test, interest in learning along learning motivation have a simultaneous effect on student achievement in class XI IPS at SMAN1 Kademangan. T table (4,16).